Leniency for Lethal Ladies: Using the Actor–Partner Interdependence Model to Examine Gender-Based Sentencing Disparities. Issue 4 (November 2019) - Fridel, Emma E.
Research has shown that female offenders typically receive differential treatment in the criminal justice system in comparison to their male counterparts, even for extreme crimes like murder. This study compares the criminal sentences of 300 homicide offenders who killed at least two victims with a single co-offender (150 pairs) within their dyads using the actor–partner interdependence model (APIM) to determine if gender has an effect on leniency for even the most extreme crimes. Women were less likely to receive the harshest possible punishment, regardless of their partner's gender. These findings provide support for the female leniency effect, suggesting that gender bias continues to influence sentencing decisions for homicide.